2015
DOI: 10.1002/cncr.29743
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing time‐driven activity‐based costing to understand the short‐ and long‐term costs of treating localized, low‐risk prostate cancer

Abstract: BACKGROUND: Given the costs of delivering care for men with prostate cancer remain poorly described, this article reports the results of time-driven activity-based costing (TDABC) for competing treatments of low-risk prostate cancer. METHODS: Process maps were developed for each phase of care from the initial urologic visit through 12 years of follow-up for robotic-assisted laparoscopic prostatectomy (RALP), cryotherapy, high-dose rate (HDR) and low-dose rate (LDR) brachytherapy, intensity-modulated radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 38 publications
2
83
0
1
Order By: Relevance
“…Other studies have focused on comparisons among surgical techniques (28)(29)(30). Perhaps the most pertinent studies have looked at the costs among various treatment modalities, including radiotherapy, surgery, or active surveillance (31)(32)(33)(34)(35)(36). Consistent with the body of literature, in vivo 32: 113-120 (2018) 118 our findings suggest that the cost of EBRT significantly outpaces the costs of surgery or brachytherapy.…”
Section: Discussionsupporting
confidence: 71%
“…Other studies have focused on comparisons among surgical techniques (28)(29)(30). Perhaps the most pertinent studies have looked at the costs among various treatment modalities, including radiotherapy, surgery, or active surveillance (31)(32)(33)(34)(35)(36). Consistent with the body of literature, in vivo 32: 113-120 (2018) 118 our findings suggest that the cost of EBRT significantly outpaces the costs of surgery or brachytherapy.…”
Section: Discussionsupporting
confidence: 71%
“…However, understanding the value of treatment with new technologies will become increasingly important as society and policy makers are moving toward accountable care organizations, bundled payments, and value-based reimbursement [59]. Since value is defined as outcomes relative to cost [60], we will need more accurate ways of capturing cost and outcomes of treatment using approaches such as time-driven activity-based costing [61] and prospective population-based prostate cancer registries [62]. We encourage clinicians and patients to participate in such registries whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause a larger discrepancy between mpMRI/TRUS fusion biopsy and TRUS biopsy at other centers in the USA. Even so, this study found that active surveillance incorporating mpMRI and MRI/ TRUS fusion biopsies is still of lowest cost when compared with other interventions for prostate cancer for at least 7 years of follow-up due to the superior detection of clinically significant prostate cancer and more appropriate selection of patients for active surveillance rather than definitive treatment [93].…”
Section: • • Cost Of Active Surveillance With Mrimentioning
confidence: 86%
“…It is important to note that mpMRI/TRUS fusion biopsy is significantly more expensive than conventional TRUS biopsy because of the higher costs associated with mpMRI for personnel and equipment, image interpretation and image handling [93]. MpMRI/ TRUS fusion biopsy was four-times higher than TRUS biopsy in one study by Laviana et al, though the study authors acknowledge that their estimated cost of MRI is significantly lower than the national average [93]. This may cause a larger discrepancy between mpMRI/TRUS fusion biopsy and TRUS biopsy at other centers in the USA.…”
Section: • • Cost Of Active Surveillance With Mrimentioning
confidence: 99%